Basic statistics for business and economics - Hoel, Paul Gerhard; Jessen, Raymond James (Santa Barbara : John Wiley & Sons, 1977)
While there are numerous texts on the market with the same goal, this text takes a practical and effective approach to engaging students with a topic that, as the author notes, they are most likely not that interested in learning. The text accomplishes this goal quite well. ... It is written in a very straightforward and understandable manner that fits its intended audience quite well. ... Given that there are dozens of introductory statistics texts on the market. it has become exceedingly difficult to create one that can be truly differentiated from the rest.
Includes index.
aia 30/04/2018
Loans
Keywords: Economics $1 (BStatistical methods.s; Statistics; Mathematical statistics